Economic, political and legal solutions to critical issues in urban education and implications for teacher preparation - Thomas, Stephanie (Professor of education); Lee, Shanique J.; Lewis, Chance W. 1972- (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"When theorizing this book, the intent was to provide an interdisciplinary look at solutions to critical issues in urban education through political, economic, and legal avenues. This book seeks to provide an interdisciplinary approach to solving the issues in education while connecting it to the effects on teacher preparation. Using historical and recent examples, scholars can piece together solutions that will guide others to political, economic, and legal action necessary to dismantle systems that have bound Black and Brown children. It is our intent to offer innovative, yet grounded solutions that can purposefully move the conversation about solutions to critical issues in education to political, economic, and legal actions"-- Provided by publisher.
Keywords: Education, Urban -- United States.; Teachers -- Training of -- United States.; Education -- Urban.; Teacher training.; Education.; Urban communities.; elektronické knihy; electronic books